Outward Bound: Strategic for Team Survival in an Organization - Ancona, Deborah (Academy of Management Journal, 1990)
Using an external perspective as a research lens, this study examined team-context interaction in five consulting teams. The data revealed three strategies toward the teams' environment: informing, parading, and probing. Informing teams remain relatively isolated from their environment; parading teams have high levels of passive observation of the environment; and probing teams actively engage outsiders. Probing teams revise their knowledge of the environment through external contact, initiate programs with outsiders, and promote their team's achievements within their organization. In this study, they were rated as the highest performers among the teams, although member satisfaction and cohesiveness suffered in the short run. Results suggested that external activities are better predictors of team performance than internal group processes for teams facing external dependence.